Identification of novel Runx1 targets involved in HSC development - Bonkhofer, F (2017)
Haematopoietic stem and progenitor cells (HSPCs) are de novo generated within in the ventral aspects of the embryonic dorsal aorta (DA). Cells of this haemogenic endothelium (HE) will eventually undergo an endothelial to haematopoietic transition (EHT) that involves cell budding out of the aortic wall. Despite the detailed description of the cellular events, the exact haemogenic lineage path and the underlying molecular mechanism that establish full haematopoietic competence are still not entirely understood. The transcription factor Runx1 is critical for the emergence of HSPCs and shows expression in the zebrafish HE as early as 24 hpf. To facilitate a detailed analysis of the transient HE population I generated a TgBAC(runx1P2:Citrine) reporter line under the control of the endogenous runx1 promoter on a bacterial artificial chromosome (BAC). Double-transgenic reporter lines for runx1 and the endothelial marker kdrl allowed us to isolate specifically cells of the DA away from the whole endothelial population, which could be further sub-divided into HE and non-haemogenic cells. Genomewide expression analysis within the respective tissues and upon Runx1 loss of function enabled the identification of HE-specific Runx1-regulated genes. Hereby, the gfi1ab gene appeared as the functional homologue of the murine Gfi1. I show that in zebrafish, EHT is orchestrated through a conserved Runx1-Gfi1-Lsd1 axis. The cellular functions of the remaining Runx1 targets imply that maturation into fully functional HSCs depends on epigenetic regulation due to the up-regulation of de novo DNAmethyltransferases, as well as on factors that allow the developing HSCs to respond to extrinsic cues from haematopoietic niches. Lastly, it became evident that the early HE expresses dll4 at similar levels to the rest of the aortic endothelium, indicating a common lineage path. In the absence of RUNX1 the HE remains essentially arterial and persists as an integrated part of the DA.